The Relevance of Applying Restorative Justice Concept in Corruption Cases With Relatively Small State Financial Losses - Nur Muttaqi, Nabila Ihza (Program Studi Hukum Pidana Islam IAIN Parepare, 2023)
This study aims to analyze the problem of corruption with relatively small financial and economic losses to the country, namely Rp. 50 million with a sentencing model that normatively relies on physical punishment, with the presence of Prosecutor's Regulation Number 15 of 2020 concerning Termination of Prosecution Based on Restorative Justice, the concept emerges only the return of state financial losses by the perpetrators of corruption by stopping the prosecution. As a normative legal research, this research uses a statute approach and a conceptual approach. Therefore, in carrying out the study it is only limited to laws and regulations related to the object to be studied and legal literature. The collected legal materials were then arranged descriptively to be analyzed qualitatively. The results of the study concluded that in the presence of the Attorney General's Regulation Number 15 of 2020 concerning Termination of Prosecution Based on Restorative Justice, it was explained that the prosecutor could terminate the prosecution of corruption cases if the perpetrators of corruption returned all financial losses and the country's economy. Convicting perpetrators of corruption with a total loss of under Rp. 50 million can be carried out by returning all financial and economic losses to the state arising from the actions of the perpetrators of corruption, so that this can make the punishment of perpetrators of corruption effective and efficient because if it still refers to physically punishing the state will actually lose more due to the costs of handling cases that are greater.